If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b in (-oo:+oo)
(1/4)*(5*b+11) = 19 // - 19
(1/4)*(5*b+11)-19 = 0
1/4*(5*b+11)-19 = 0
1/4*(5*b+11)-19 = 0
5/4*b-65/4 = 0
5/4*b-65/4 = 0
5/4*b-65/4 = 0 // + 65/4
5/4*b = 65/4 // : 5/4
b = 65/4/5/4
b = 13
b = 13
| (1/4)(5-2h)=(h/2) | | .5y=19y | | -9x=-3 | | (1/4)(4x+3)=4 | | (1/4)(4)=1 | | (1/4)(3x+1)=3x | | 7/9h=28 | | (1/4)(3t+27)=(3/4)(3t+15) | | 0.2x+0.4x=24 | | (1/4)(2x-16)=3x+11 | | (1/4)(2x+72)=5x | | (1/4)(13x+6)=(1/3)(7x-1) | | (1/4)(12-4t)=27 | | 5x^2+15x-10=0 | | (1/3y-2/3)(1/4y-3/2)=0 | | (1/3y)-2=(1/2y) | | (1/3x+9)-(2/x+3)=2 | | (6-27x)=(3+2x) | | (1/3x)=12 | | (1/3x)=(4/9) | | (1/3x)=(2/5X)+(2/3) | | (1/3x)-1=(4/5x)+(1/6) | | (1/3x)-(5/12)=(5/6x)-(11/12) | | (1/3x)+(2/9)-3x=(-22/9) | | (1/3x)+(2/5x)+60=x | | (1/3x)+(1/4)=(1/6)-x | | (1/3b)-(1/2b)=1/6 | | 60=a/1-0.4 | | (1/3b)+3=(1/2b) | | (1/3+4v)(1/11-5v)=0 | | (1/3)z=3z-(4/5) | | 60=a/1.4 |